Special issue: Pharmaceutical innovation - Pornsak Sriamornsak; Duangratana Shuwisitkul (Asian Journal of Pharmaceutical Sciences, 2018)
“Pharmaceutical innovation” is an interdisciplinary area of the pharmaceutical sciences including drug development with a focus on manufacturing, process control, and technology, among many other subfields of research. In this special issue, we have invited all participants attended the International Conference and Exhibition on Pharmaceutical Sciences and Technology 2018 under the theme of pharmaceutical innovation and translational research for human health, held in Bangkok during January 24–25, 2018, to submit the research papers and after peer-review process, 10 of them were selected. Keywords: Pharmaceutical innovation, Dosage form design, Pharmaceutics